THE AUGMENTED REALITY (AR) INSERTION IN MOBILE LEARNING PROCESS FOR SMARTPHONES: A BRIEF ANALYSIS THROUGH SYSTEMATIC LITERATURE REVIEW (RSL) - Bernert Puppi, Maicon; Fadel, Luciane Maria (International Congress of Knowledge and Innovation - Ciki, 2023)
Applying a systematic review we investigate the insertion of Augmented Reality (AR) technology in the mobile learning process via smartphone. The results point to a greater frequency of works that analyze only AR, leaving m-learning as a secondary process. Among the aspects identified regarding the insertion of AR in m-learning, the following stand out: (1) AR is only justified in m-learning when there are common objectives between the two projects (technology and process); (2) AR embedded in m-learning can bring greater motivation and increase user collaboration; (3) to represent complex and abstract concepts (from AR) in contexts of ubiquity (from m-learning); (4) being able to explore the location-based-learning as a kind of learning; (5) there is a gap of projects of this type for the elementary school, which can be exploited.